Моделирование процесса просеивания влажного минерального сырья - Надутый, Владимир Петрович; Лапшин, Е. С. (НТУ "ХПИ", 2007)
Запропоновано вібраційне просівання вологої сировини моделювати ймовірнісним процесом влучення частки в отвір сита й процесом коливання частки на капілярному містку. Отримано нелінійне диференціальне рівняння коливань частки. На основі чисельного рішення сформульована умова просівання частки через отвір сита, що дозволяє визначити необхідну амплітуду й частоту коливань.

It is offered to model vibrational screening wet raw material a probabilistic process of hit of a corpuscle in a mesh and process of oscillation of a corpuscle on the capillary walkway. The nonlinear differential equation of oscillations of a corpuscle is gained. On the basis of a numerical solution the condition of screening of a corpuscle through a mesh which allows to define demanded amplitude and an oscillation frequency is formulated.
Keywords: вибрационное грохочение; просеивание; частицы; жидкость; сито; коэффициент поверхностного натяжения; амплитудно-частотные характеристики; минеральное сырье